The life-cost cycle-based sizing of complementary energy storage technologies in DC microgrids - Dunya Sh. Wais; Huda A. Abbood; Radhi Sehen Issa (International Journal of Electrical and Computer Engineering (IJECE), 2026)
Hybrid energy storage system (HESS) configurations have the potential to mitigate the detrimental effects of photovoltaic power generation oscillations on DC microgrid safety and reliability. The economic efficiency of HESS can be improved through the utilization of batteries and their complementary attributes through an energy management strategy. This will allow for the full utilization of the benefits of superconducting magnetic energy storage (SMES), such as high efficiency, lossless energy storage, elevated power density, and rapid response. The battery-SMES HESS is subject to a life cycle cost (LCC) model, along with its associated constraints. System expenditures can be drastically cut by optimizing the HESS capacity layout. The goal function is the lowest LCC, presuming that the power demands of the system are met. Particle swarm optimization takes acceleration into account when designing the capacity of the system. In order to prove that the suggested method of configuring capacity works, a microgrid model is created and tested using numerical data.